AZIZIDDIN NASAFI’S SUFI ONTOLOGY AND HIS APPROACH TO ONTOLOGICAL CONCEPTS (Scientific journal of the Fergana State University, 2026)
This article analyzes the views of Azizuddin Nasafi, a prominent representative of medieval Sufi doctrine and philosophy, one of our great ancestors, on the ontology of Sufism. It also provides information about the Sufi's attitude to the ontological concepts put forward by thinkers and teachings in the history of Sufism and philosophy, as well as his own independent position.